Analiza wybranych projektów unijnych jako wyraz zaangażowania państw UE w rozwój narzędzi ITC i technologii językowych w nauczaniu języków obcych - Borowiak-Dostatnia, Marta; Zięba, Anna (Neofilolog, 2019)
The paper presents a sample of analysis of EU project with regard to ICT application in foreign language teaching and language technology. The analysis is based upon the authors’ observation that by exploring a number of at least 75 projects in terms of their participants, framework programs and scope, some general tendencies can be revealed. The tendencies concern EU research and member state engagement in the aforementioned fields. Having analyzed the data the authors define the nature of the studied projects (educational vs. scientific), point to the most active and beneficial member states and draw models of public and private units cooperation in European research consortiums. Additionally, the analysis presents the first step for further study with regard to particular ICT-tool usage in foreign language learning/teaching in a particular EU country.